Anselm on Freedom. By Katherin A. Rogers - Evans, Gillian (The journal of theological studies, 2009)
It is not easy to write on these well-worn themes in Anselm with fresh insight. This book is something new. The trick is to find a new way to pose a perennial question of Christian theology. Rogers has done this by proposing a theory she labels ‘compatibilism’. Her hypothesis is that ‘any instance of choice which is causally necessitated by factors outside of the agent, whatever those factors may be, raises the key question: can the agent be held morally responsible for a choice of which the ultimate cause lies outside himself?’ Augustine, she argues, says yes. Anselm says no (p.